2016
DOI: 10.1016/j.carpath.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 (Gilenya) treatment prevents spontaneous autoimmune myocarditis and dilated cardiomyopathy in transgenic HLA-DQ8-BALB/c mice

Abstract: Although dilated cardiomyopathy (DCM) is often caused by viral infections, it frequently involves autoimmune mechanisms associated with particular HLA-DR and DQ alleles. Our homozygous HLA-DQ8.Ab0 transgenic mice in the BALB/c background (HLA-DQ8BALB/c-Tg) developed early and progressive fatal heart failure from 4–5 weeks of age. Clinical signs of the disease included cyanotic eyes, tachycardia with dyspnea, from pale to cyanotic limbs and terminal whole body edema. Sick mice had extremely dilated hearts, enla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…This idea was functionally confirmed by introducing specific HLA complexes into a mouse. Replacement of mouse MHC class II with the specific HLA-DQ8 in NOD or BALB/c mice resulted in spontaneous development of myocarditis and iDCM phenotype (without evident fibrosis), and were associated with cardiac arrhythmias and high mortality of the transgenic mice (176180). This model resembles a course of fatal fulminant myocarditis in humans.…”
Section: Mouse Models Of Experimental Myocarditismentioning
confidence: 99%
“…This idea was functionally confirmed by introducing specific HLA complexes into a mouse. Replacement of mouse MHC class II with the specific HLA-DQ8 in NOD or BALB/c mice resulted in spontaneous development of myocarditis and iDCM phenotype (without evident fibrosis), and were associated with cardiac arrhythmias and high mortality of the transgenic mice (176180). This model resembles a course of fatal fulminant myocarditis in humans.…”
Section: Mouse Models Of Experimental Myocarditismentioning
confidence: 99%
“…In recent years, with the gradual deepening of research on the SphK/S1P/S1PRs signal axis and FTY720, a number of studies have shown that the S1PRs modulator FTY720 has significant protective effects in autoimmune myocarditis, uveal retinitis, systemic lupus erythematosus, atherosclerosis, and other models. 20–23 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the gradual deepening of research on the SphK/S1P/S1PRs signal axis and FTY720, a number of studies have shown that the S1PRs modulator FTY720 has significant protective effects in autoimmune myocarditis, uveal retinitis, systemic lupus erythematosus, atherosclerosis, and other models. [20][21][22][23] FTY720 and DM DM is one of the most common metabolic diseases in humans and is characterized by a reduction in the mass of functional islet β cells and insulin resistance. Previous studies have shown that the function and survival of islet β cells and insulin sensitivity play important roles in DM, both of which are regulated by the S1P signaling axis.…”
Section: Introduction To Fty720mentioning
confidence: 99%